Exogenous nitric oxide promotes salinity tolerance in plants: A meta-analysis - Tahjib-Ul-Arif, Md.; Wei, Xiangying; Jahan, Israt; Hasanuzzaman, Md.; Sabuj, Zahid Hasan; Zulfiqar, Faisal; Chen, Jianjun; Iqbal, Rashid; Dastogeer, Khondoker M. G.; Sohag, Abdullah Al Mamun; Tonny, Sadia Haque; Hamid, Imran; et al. (Frontiers in Plant Science, 2022)
Nitric oxide (NO) has received much attention since it can boost plant defense mechanisms, and plenty of studies have shown that exogenous NO improves salinity tolerance in plants. However, because of the wide range of experimental settings, it is difficult to assess the administration of optimal dosages, frequency, timing, and method of application and the overall favorable effects of NO on growth and yield improvements. Therefore, we conducted a meta-analysis to reveal the exact physiological and biochemical mechanisms and to understand the influence of plant-related or method-related factors on NO-mediated salt tolerance. Exogenous application of NO significantly influenced biomass accumulation, growth, and yield irrespective of salinity stress. According to this analysis, seed priming and foliar pre-treatment were the most effective methods of NO application to plants. Moreover, one-time and regular intervals of NO treatment were more beneficial for plant growth. The optimum concentration of NO ranges from 0.1 to 0.2 mM, and it alleviates salinity stress up to 150 mM NaCl. Furthermore, the beneficial effect of NO treatment was more pronounced as salinity stress was prolonged (>21 days). This meta-analysis showed that NO supplementation was significantly applicable at germination and seedling stages. Interestingly, exogenous NO treatment boosted plant growth most efficiently in dicots. This meta-analysis showed that exogenous NO alleviates salt-induced oxidative damage and improves plant growth and yield potential by regulating osmotic balance, mineral homeostasis, photosynthetic machinery, the metabolism of reactive oxygen species, and the antioxidant defense mechanism. Our analysis pointed out several research gaps, such as lipid metabolism regulation, reproductive stage performance, C4 plant responses, field-level yield impact, and economic profitability of farmers in response to exogenous NO, which need to be evaluated in the subsequent investigation.